Aspectos ergonômicos e biomecânicos da atividade de manuseio de carga com ênfase no membro superior - Oliveira, Ana Beatriz de (Universidade Federal de São Carlos, 2008)
Despite the large tendency to task automation, manual material handling (MMH) is still performed in occupational settings. This activity has been widely studied but the focus has been kept on the low back. Besides the lower back, the incidence of musculoskeletal disorders also on upper limb, among workers who perform MMH, shows that there is a need to achieve a better understanding on the interaction between this segment and physical risk factors in the workplace. Besides physical factors, the musculoskeletal load during the MMH seems to be also influenced by the workers experience. In order to contribute with information on the effects of workplace factors on the upper limb behavior during MMH, two studies were developed. The objective of the first study was to evaluate the effects of height of the target surface and load mass on the muscular activity and movements during MMH performed by experienced and inexperienced subjects. Both muscular activity and movements were influenced by the variation of the load mass and height of the target surface. However, there was any difference for the comparison between experienced and inexperienced subjects. This fact was probably related to the homogeneity of the grip used by the subjects to carry out the handling, which has probably an association with the design of the box used in the experiment. In order to better understand the characteristics of the grip used by the subjects to perform the task, another study was conduced. The objectives were (1) to evaluate how experienced and inexperienced subjects would grasp a box when all sides were free to be approached; (2) to describe grip force and wrist movements according to each kind of hand grip, attempting to different heights of the destination surface; (3) to check for safe range of motion recorded for wrist movements in all conditions. Wrist movements and grip force were recorded during the task. Experienced and inexperienced subjects grasped the box by placing their hands on the lateral side and fingers on bottom side. This pattern was observed in all assessed conditions. It seems that when the box allows the free access to the bottom side, both experienced and inexperienced subjects prefer to use that side to position their hands/fingers. Data on movements and grip force has suggested that this grip can provide biomechanical advantage and should be available in occupational settings. In general, the results have shown that physical factors, like height of target surface and load mass, are determinants on the musculoskeletal load. Considering the demand required from the upper limbs, the high surface (around shoulder level) seems to produce higher risk to the development of disorders on this segment. To provide a better understanding on the upper limbs load, studies considering different layouts, as well as asymmetrical tasks and real occupational settings should be conduced.
Keywords: Fisioterapia preventiva; Ergonomia; Manuseio de carga; Ombro; Eletromiografia; Postura; Manual material handling; Shoulder; Electromyography; Posture; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL